NONLOCAL (IN TIME) PROBLEM FOR THE EVOLUTIONARY EQUATION WITH FRACTIONAL DIFFERENTIAL OPERATOR - Horodets’kyi, V.V.; Kolisnyk, R.S.; Shevchuk, N.M. (My University, 2023)
We establish the correct solvability of a multipoint nonlocal (in time) problem for the evolutionary equation with operator of fractional differentiation and an initial function, which is an element of the space of generalized functions of the distribution type. The analytic representation of the solution is presented. We also analyze the behavior of the solution in the case of unlimited growth of the time variable (stabilization of the solution).
Keywords: evolutionary equation